2021
DOI: 10.1177/03611981211005777
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mobile Terrestrial LiDAR Scanning Systems for Identification of Potential Pavement Rutting Locations

Abstract: Periodic measurement and identification of the presence and severity of pavement rutting are crucial for pavement management programs conducted by state transportation agencies. This paper proposes a novel analytical method for identifying pavement rutting locations using data collected by mobile terrestrial LiDAR scanning (MTLS). Four vendor MTLS systems were evaluated based on their ability to accurately reproduce a roadway’s transverse profile. To establish ground-truth measurements, 2 in. interval pavement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Other proposals take advantage of the detailed point clouds obtained through MLS to analyze surfaces in detail, as shown in the work of Famili, where pavement rutting is detected by fitting a surface from which features such as aspect, slope, and plan and profile curvatures can be computed (Famili, 2020). Cai and Rasdorf (2008) concluded that LIDAR point clouds could be directly used in modeling linear objects in a 3D space instead of being interpolated into traditional elevation data.…”
Section: Related Workmentioning
confidence: 99%
“…Other proposals take advantage of the detailed point clouds obtained through MLS to analyze surfaces in detail, as shown in the work of Famili, where pavement rutting is detected by fitting a surface from which features such as aspect, slope, and plan and profile curvatures can be computed (Famili, 2020). Cai and Rasdorf (2008) concluded that LIDAR point clouds could be directly used in modeling linear objects in a 3D space instead of being interpolated into traditional elevation data.…”
Section: Related Workmentioning
confidence: 99%
“…To analyze rut depth, transverse profiles of the LIDAR point clouds are essential. In [14] transverse profiles were evaluated using partial curve mapping, Fre'chet distance, area, curve length, and dynamic time warping techniques. They came up with a novel technique to identify rutting locations by analyzing the curvature of mobile terrestrial LiDAR systems raster surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Light detection and ranging (LiDAR) techniques may provide an efficient and practical solution for addressing this difficult challenge ( 9 – 13 ) using low altitude airborne LiDAR scanning (ALS) and mobile terrestrial LiDAR scanning (MTLS). By adopting MTLS technology, departments of transportation could potentially experience significant savings on the cost of cross slope verification, and possibly reduce contract time for commonly administered pavement rehabilitation projects by four to six months ( 8 ).…”
mentioning
confidence: 99%